States of Legal Denial: How the State in Myanmar Uses Law to Exclude the Rohingya. Issue 1 (1st January 2021) - Crouch, Melissa
ABSTRACT: States often use forms of denial to suppress the pain and suffering of minority groups. In 2015, the international community celebrated the electoral success of the National League for Democracy in Myanmar. Yet through legislative reform, the Rohingya were disenfranchised prior to the election. This is an example of legal denial, that is, the use of law and legal institutions to enact denial. The article traces three uses of legal denial against the Rohingya. One act of legal denial is constitutional reform through the creation of Rakhine State in 1974 and the making of the Rohingya as a minority within Rakhine State. Another act of legal denial is legislative reform through the removal of the right to vote and run for office in 2015. A further means of legal denial occurs through judicial decision-making and the use of political trials related to the conflict in Rakhine State. As the global community struggles with how to respond to the violence, displacement and humanitarian crisis, it is suggested that there is a need to understand the acts of legal denial – constitutional, legislative and judicial – that led to this crisis and how these acts of denial are employed to deny suffering and violence.